Finite element analysis of a coconut (Cocos nucifera l.) climbing mechanism - Afan, Arjay O.; Zubia, Omar F.; Borja, Adrian A.; Gallegos, Ralph Kristoffer B. (2023)
A coconut climber mechanism was subjected to Finite Element Analysis (FEA) to improve its overall design and analyze its strength characteristics. The von Mises stress, total deformation, and factor of safety were evaluated using static structural analysis for the seat and pedal assemblies of the mechanism. The design has a minimum yielding factor of safety of 7.03 for the seat assembly and 12.09 for the pedal assembly. If aluminum is used as an alternative to steel, the prototype's weight can be reduced to at least 64.56% without compromising its strength properties. The weight reduction by using aluminum is expected to reduce the effort required to use the improved designs. This study also demonstrated a robust methodology of exploring design alternatives without fabricating actual prototypes, leading to a more cost-effective design process. It is recommended that other topologies and materials be further explored to improve the design of the coconut climber mechanism.
Keywords: Coconut -- Processing -- Machinery